CINDERELLA COMPLEX ON MILLENNIAL STUDENTS - Fahmi Nur Abidah; Dyah Siti Septiningsih (PSIMPHONI, 2022)
Women and men have differences, in a biological perspective, psychological and social perspectives. Social perspective, women are educated to be gentle and shows the feminine side, while men are educated to be masculine. Students who are known for being confident and having an out of the mind box in fact, especially female students have fear and psychological dependence, as well as a desire to be protected known as the Cinderella complex. Cinderella complex is fear women are not aware of the independence and success that causes herself to have a tendency to be protected by others especially men. This study aims to examine the Cinderella complex in college students millennial women. This study uses a qualitative research method with a case study. Data collection is done through semistructured interviews to 3 primary informants and 3 secondary informants credibility of using triangulation of sources. Data analysis using interactive model data analysis. The findings of this study are that the three female students unconsciously experiencing cinderella complex syndrome shown with social behavior, namely, happy to receive attention from many men, have a tendency to depend on and be influenced by others, communication is not assertive, not confident in their abilities and rely on luck in determining the success factor. The factors of these behavior are parenting factors, personal maturity, and selfconcept influenced by parenting factors, personal maturity and self-concept.